2019
DOI: 10.1136/bjsports-2019-100709
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of early controlled motion of the ankle compared with immobilisation in non-operative treatment of patients with an acute Achilles tendon rupture: an assessor-blinded, randomised controlled trial

Abstract: BackgroundEarly controlled motion (ECM) of the ankle is widely used in the non-operative treatment of acute Achilles tendon rupture, although its safety and efficacy have not been investigated properly in a randomised set-up.Purpose/Aim of the studyTo investigate if ECM of the ankle was superior to immobilisation in the treatment of acute Achilles tendon rupture.Materials and methodsThis was an assessor-blinded, randomised controlled trial with patients allocated in a 1:1 ratio to one of two parallel groups. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 42 publications
4
51
0
Order By: Relevance
“…The authors found no evidence of a diference in func tional outcome. One further study, published in 2019, 28 randomly allocated 130 patients to cast immo bilisation or early controlled motion at a single centre. The authors found no evidence that early controlled motion was of benefit compared with immobilisation in any of the investigated outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found no evidence of a diference in func tional outcome. One further study, published in 2019, 28 randomly allocated 130 patients to cast immo bilisation or early controlled motion at a single centre. The authors found no evidence that early controlled motion was of benefit compared with immobilisation in any of the investigated outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is either surgical or non‐surgical, and these modes involve different immobilization periods 4‐6 . Early mobilization seems to lead to better functional outcomes, a higher quality of life and a shorter rehabilitation period 7‐10 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the present trial has chosen a functional outcome as the primary outcome. In contrast, several previous randomized controlled trials have used patient-reported outcome measures as primary outcomes [4,12,31]. However, their results have shown the patients to have an acceptable score within the patient reported outcome measures but markedly low scores among the tests of physical function.…”
Section: Discussionmentioning
confidence: 96%